High Neutrophil-lymphocyte Ratio Predicts Serious Renal Insufficiency in Patients with Lupus Nephritis - Dijiao Tang; Qi Tang; Long Zhang; Hongxu Wang (Iranian Journal of Immunology, 2022)
Background: Lupus nephritis (LN) is one of the most serious complications of systemic lupus erythematosus (SLE).The neutrophil to lymphocyte ratio (NLR) is a promising predictor and prognostic factor. An increased NLR is associated with a poor prognosis of several inflammatory diseases. Objective: To evaluate the value of NLR in the diagnosis and pre-assessment of the disease severity of LN. Methods: This retrospective study included 88 patients with LN, 51 SLE patients without kidney involvement, 79 patients with primary chronic nephritis (CN), and 52 healthy controls (HC). The differences among these four groups and diagnostic value of NLR for patients with LN were evaluated. Results: The NLR of patients with LN before treatment was significantly higher than that of the other three groups. NLR positively correlated with C-reactive protein (CRP), complement 3(C3), C4, and serum creatinine (SCr) (CRP: r=0.337, p=0.007; C3: r=0.222, p=0.042; C4: r=0.230, p=0.035; SCr: r=0.408, p <0.0001) but negatively correlated with total serum IgG (r=-0.226, p=0.041). The level of NLR increased with the severity of renal dysfunction NLR (area under the curve: 0.785, 95% CI: 0.708-0.862) was useful for the diagnosis of LN, and its optimal cut-off value was 5.44 (sensitivity: 65.9%, specificity: 86.3%). Conclusions: NLR would be useful for the diagnosis of LN and reflects the severity of renal dysfunction Therefore, evaluating NLR before treatment could help clinicians to identify potential renal involvement in patients with SLE and distinguish LN from CN.